Students’ Understanding of Anti-Bullying Education in Increasing Social Awareness - Amara P. B. Natania; Alvina Rahmawati; Zalfaa A. Khonsa; Naumi M. Amanda; Ayatullah Maulidy (Al-Qalam Institute, 2026)
Bullying remains a persistent problem in schools, indicating that anti-bullying education often fails to translate into meaningful social awareness among students. This study aims to examine how students interpret anti-bullying education and how these interpretations contribute to the Development of social awareness. Employing a qualitative case study design, the research involved 24 fifth-grade students and used open-ended interviews, reflective written responses, observations, and documentation analysis. The findings reveal three interrelated themes: students internalized bullying as a form of moral wrongdoing, demonstrated empathetic peer awareness through consistent social behaviors, and expressed pro-social responsibility through written and visual commitments such as pledges and posters. These results show that students’ cognitive and moral meaning-making processes play a decisive role in shaping ethical judgment, empathy, and responsible action. The novelty of this study lies in highlighting students as active interpreters of anti-bullying education rather than passive recipients of program messages. The findings suggest that anti-bullying initiatives should prioritize reflective, empathy-based, and participatory strategies to promote sustained social awareness and positive peer relations.